ALIH KODE PADA PERCAKAPAN SISWA SMA NEGERI 1 ADONARA BARAT KABUPATEN FLORES TIMUR - Selviana Ina Waiwuring, Maria; Pande, Rikardus; Yolanda Mario Leu, Yoakim (Social Science Academic, 2023)
This study aims to describe the conversational code switching of SMA Negeri 1 Adonara Barat, East Flores district. The theory used is sociolinguistic theory. The method used is a qualitative method. The research data is in the form of student conversations. The data source is Adonana Barat 1 Public High School students who are having a conversation. The results of this study indicate (1) the form of language code switching in the conversations of students of SMA Negeri 1 Adonara Barat is internal code switching and external code switching, (2) the causes of language code switching in the conversations of students of SMA Negeri 1 Adonara Barat are, code switching is not directly to the interlocutor, the influence of the speaking situation, the influence of the presence of a third person, and the influence of language practice.